Nelson essentials of pediatrics - Marcdante, Karen J.; Nelson, Waldo E. (Waldo Emerson), 1898-1997. (Philadelphia, PA : Saunders/Elsevier, 2011)
Contents: The profession of pediatrics -- Growth and development -- Behavioral disorders -- Psychiatric disorders -- Psychosocial issues -- Pediatric nutrition and nutritional disorders -- Fluids and electrolytes -- The acutely ill or injured child -- Human genetics and dysmorphology -- Metabolic disorders -- Fetal and neonatal medicine -- Adolescent medicine -- Immunology -- Allergy -- Rheumatic diseases of childhood -- Infectious diseases -- Digestive system -- Respiratory system -- Cardiovascular system -- Hematology -- Oncology -- Nephrology and urology -- Endocrinology -- Neurology -- Dermatology -- Orthopedics.
Includes bibliographical references and index.
Keywords: Pediatrics; Pediatrics